2021
DOI: 10.1186/s13045-021-01204-0
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine reader IMP2 stabilizes the ZFAS1/OLA1 axis and activates the Warburg effect: implication in colorectal cancer

Abstract: Background Accumulating evidence shows that N6-methyladenine (m6A) modulators contribute to the etiology and progression of colorectal cancer (CRC). However, the exact mechanisms of m6A reader involved in glycolytic metabolism remain vague. This article aimed to crosstalk the m6A reader with glycolytic metabolism and reveal a new mechanism for the progression of CRC. Methods The relationship between candidate lncRNA and m6A reader was analyzed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…In addition, lncRNA LINRIS stabilizes IGF2BP2 by blocking its ubiquitination to promote the c-MYC-driven glycolysis in colorectal cancer 157 . In colorectal cancer, IGF2BP2 directly binds to the m 6 A sites of lncRNA ZFAS1 and increases its stability to activate the Warburg effect 158 . Moreover, LINC01021 promotes tumorigenesis and progression through enhancing the mRNA stability of target transcripts, MSX1 and JARID2 in IGF2BP2- mediated m 6 A modification 159 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…In addition, lncRNA LINRIS stabilizes IGF2BP2 by blocking its ubiquitination to promote the c-MYC-driven glycolysis in colorectal cancer 157 . In colorectal cancer, IGF2BP2 directly binds to the m 6 A sites of lncRNA ZFAS1 and increases its stability to activate the Warburg effect 158 . Moreover, LINC01021 promotes tumorigenesis and progression through enhancing the mRNA stability of target transcripts, MSX1 and JARID2 in IGF2BP2- mediated m 6 A modification 159 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…Interestingly, one recent genome-wide analysis of lncRNA half-lives in humans revealed that RBP-lncRNA interactions mainly enhance the stability of lncRNA with only one exon [ 22 ]. Additionally, N6-methyladenosine (m6A) writers and erasers, as well as readers, are all RBPs that modulate m6A modification and function of lncRNAs [ 23 ], primarily by affecting their stability and changing their expression levels [ 24 , 25 , 26 ]. Recently, RBP has also been reported to regulate the transcription of lncRNA.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA-133b/SF3B4 axis may serve as a new immunotherapeutic target for HCC treatment (54). The other hub genes (e.g., YBX1, OLA1, TRMT10C, and KIF20A) also play a key role in the development and prognosis of the pan-cancer section (55)(56)(57)(58). Meanwhile, the role of TIMM23, YARS1, and EIF2S1 in affecting HCC is still unclear.…”
Section: Discussionmentioning
confidence: 99%